Dynamic modeling and simulation of power systems with high-level wind power generation - Luo, Ye (Nanyang Technological University, 2020)
The potential energy crisis, power shortage and other issues have become increasingly prominent. However, wind power is one of the most important clean renewable energy resources for the modern society. It is of great significance to alleviate energy shortage problems. The continuous advancement of wind power technology, the capacity of units increases. Many countries have successively introduced policies to encourage wind power as well as the proportion of grid-connected wind farms in the power grid system. Thus, a lot of relative research topics emerges following the trend. It is necessary to do some in-depth study of grid-connected wind farms. This dissertation work introduces the development of dynamic model and the performance of a time-domain simulations for power system with and without wind power resources. The dynamic simulation cases exam the voltage response of the power system under various wind power penetration proportions with different fault scenarios. All the simulation is conducted in the PSS/E simulation environment. The power system constructed in this paper work is named Nordic-74 system under the instruction of IEEE Power & Energy Society guidebook, as a novel variant of existed Nordic-32 power system. Typically, the Type 4 wind turbine model is adapted in the simulation. According to the construction and analyses on different dynamic simulation cases, the Nordic-74 power system feasibility and dynamic performances are presented, providing a possible approach to enrich the research concerning the modern power system with renewable energies.